Micromolded Polylactid Acid With Selective Degradation Rate - Iozzino, Valentina; De Meo, Annarita; Pantani, Roberto (Frontiers in Materials, 2019)
Poly(Lactic Acid), PLA represents a very interesting polymer for industrial applications because of its good processability, the possibility of being obtained from renewable sources, good physical properties, biocompatibility, and biodegradability. The major depolymerization mechanism and the step that controls the rate of PLA biodegradation in compost is represented by the hydrolysis. The characteristic of being degradable is not per se an advantage: the inclination to degrade in the presence of water represents a limit for specific industrial applications, especially for durable components that are designed for long-period utilization such as in the automotive, electronic, and agricultural sectors, as well as in medical applications. Being able to control the degradation rate would be a real advantage: a product should preserve its characteristics during processing and for a time comparable to its application but should be nevertheless fully biodegradable at longer times. Furthermore, a gradient of properties could allow producing samples in which some portions degrade at a faster rate and some others at a slower one. Different methods can be used to influence the degradation rate of PLA, some examples are blending, copolymerization and surface modification. However, these change the physical properties of the material. Any factor influencing the rate of hydrolysis can affect the biodegradation process. The objective of this work is verifying the possibility to modulate the rate of degradation in the same part, in time and at different rates. The method is represented by a technique that influences locally the morphology of the samples. Biphasic samples (half amorphous and the other half crystalline) were obtained by micro-injection molding and the degradation process was monitored by means of hydrolysis tests. The analysis confirmed the crystalline regions show a slightly better resistance to the hydrolysis compared to the amorphous.